Efektivitas Penggunaan Motion Graphic Sebagai Media Pembelajaran Augmented Reality Pada Program Studi Teknologi Informatika Multimedia Digital Politeknik Negeri Sriwijaya - Adi Sutrisman (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Abstract Motion graphics are often used to describe various graphic design solutions to create a dynamic and effective communication design to convey information. Making Augmented Reality learning media based on motion graphic animation. This learning media will be delivered in the Enterprise Social Multimedia Practicum and Augmented Reality Practicum courses in the Digital Multimedia Information Technology Study Program. The methodology used in making this learning media is the Luther method and the Likert Scale. Making learning media for making augmented reality uses a type of animation in the form of motion graphics, producing a video of 9 minutes 20 seconds in *mp4 format. Based on the results of data analysis obtained from alpha and beta respondents, it can be seen that the animated video motion graphic learning media for making Augmented Reality provides information that is easy to understand so that it can be used as a learning medium. Keywords: Media, Augmented Reality, Motion Graphic